Strona 1 z 1

Rozwiąż równanie.

: 7 gru 2008, o 14:46
autor: wielkidemonelo
\(\displaystyle{ tg5x=tg11x}\)

\(\displaystyle{ \frac{sin5x}{cos5x}- \frac{sin11x}{cos11x}=0}\)


\(\displaystyle{ \frac{sin5xcos11x-sin11xcos5x}{cos5xcos11x}=0}\)


\(\displaystyle{ \frac{sin(5x-11x)}{cos5xcos11x}=0}\)

Jak rozłożyć mianownik i czy \(\displaystyle{ sin(5x-11x)= sin(-6x)=-sin6x}\)?
Aha, rozumiem, że mianownik możemy odrzucić, tak?
Także \(\displaystyle{ -sin6x=0}\)
\(\displaystyle{ sin6x=0}\)
\(\displaystyle{ 6x=k\pi}\)
\(\displaystyle{ x= \frac{k\pi}{6}; k C}\)
Dzięki za waszą nieocenioną pomoc.